(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: This research moved from the initial observation that the application by the amah Village Autonomy Law. No. 6 Year 2015 About the Village is not optimal so that the impact on the low participation of rural communities, especially in the district of South Sorong Regency Saifi. Thus, this study aimed to analyze the effect of implementation of village autonomy to public participation in the development of Saifi village in the district of South Sorong regency. Denagn applying the method of descriptive and quantitative approaches and applying imntrumen questionnaire, distributed to 46 people selamnjutnya government officials Kampung distributed into five villages. After the data and information collected, then processed and analyzed by using frequency tables and analysis product moment correlation analysis and simple linear regression to test the hypothesis. The results of data analysis menunkkan that (1). The implementation of village autonomy is in the category "medium" tend to be "low", while the level of community participation in rural development are in the category of "moderate" tend to be "high". (2). The implementation of village autonomy as one of the factors that influence people’s participation in rural development. The implementation of village autonomy contribute positively and significantly on the level of participation of rural communities, especially in the district of South Sorong Regency Saifi. Thus, it can be concluded that the hypothesis can be tested by empirical validity as well as to justify the underlying theories. It is necessary to give some suggestions, among others: (1). Not optimal application of Village Autonomy, it is expected that the government (district / city and province) is committed to delegate authority under the legislation in force regarding some matters that are directly handled by the village government so as to encourage an increase in the intensity of the implementation of village autonomy. (2). It is recommended that the local government encourages well as streamline the functions of village institutions as a partner with the village government through education and functional training. Keywords: Autonomy village, community participation, rural development